Dynamics of the canine gut microbiota of a military dog birth cohort - An, Jae-Uk; Mun, Seung-Hyun; Kim, Woo-Hyun; Seong, Je Kyung; Park, Kyoungwan; Cho, Seongbeom (Frontiers in Microbiology, 2025)
IntroductionWe systematically tracked early life stages in a military dog birth cohort to investigate canine gut microbiota dynamics related to environmental exposure during growth. This study utilized 16s rRNA amplicon sequencing-based analysis with molecular epidemiology of Enterococcus faecalis within a controlled environment at a military dog training center.MethodsWe examined shifts in gut microbiota diversity and taxonomic composition across four growth stages (lactation, weaning, starter, puppy) in three littermate groups. Additionally, E. faecalis dynamics was analyzed to confirm strain sharing among littermate groups.ResultsGut microbiota changed rapidly during early growth, stabilizing at the puppy stage. This is supported by increased similarity in taxonomic composition among littermate groups, as they experienced an increased shared external environment and consumed the identical diets. E. faecalis strain sharing among littermate groups increased as dogs aged. Nine E. faecalis cluster types were identified; three specific types (type I, II, and IX) dominated in each littermate group during lactation. With greater exposure to the shared external environment, cluster type I gradually assumed dominance across all groups. Despite the dynamic shifts in microbiota, we found five genera within the core microbiota, Bacteroides, Peptoclostridium, Fusobacterium, Lactobacillus, and Blautia.DiscussionThis study is the first to explore the dynamic nature of early-life canine gut microbiota, illustrating its transition to stability and its resilience to environmental perturbations within the controlled training environment of a military dog birth cohort.